COMMUNITY EMPOWERMENT IN STUNTING PREVENTION THROUGH THE INTRODUCTION OF ORGANIC FARMING SYSTEMS IN KOYA KOSO VILLAGE, ABEPURA DISTRICT, JAYAPURA CITY - Tuhuteru, Sumiyati; Inrianti, Inrianti; Rumbiak, Rein Edward Yohanes; Pumoko, Patras; Kogoya, Geztha Nathan (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Stunting still be one of necessary state problems completed. Government through Long Term Development Plan National Medium Term Development Plan (RPJMN) 2020-2024, also sets a national stunting target so that it can down reached 14%. This is refers to the Sustainable Development Goals (SDGs) agenda. Talking about the need food and nutrition fulfilled always started with attention to type food consumed​ as well as source origin food consumed. For​ that, in increase food quality required by the relevant community​ with prevention of stunting then needed introduction in development system agriculture organic for avoid pattern consumption contaminated food​ with material chemicals contained​ in product cultivated agriculture​ farmers. For this reason, community empowerment activities in preventing stunting through the introduction and development of organic farming need to be carried out. The method used in implementing this community service activity uses the ABCD (Asset Based Community Development) approach to achieve the goal of preventing stunting that is right on target through counseling on the introduction and development of organic farming systems. The implication of this service activity is that there is an increase in community knowledge and understanding of stunting prevention. Farmer groups also know and understand how to make liquid organic fertilizer from household waste.